Proteome analysis reveals the important roles of protease during tenderization of sea cucumber Apostichopus japonicus using iTRAQ. (May 2020) - Dong, Xiufang; He, Baoyu; Jiang, Di; Yu, Chenxu; Zhu, Beiwei; Qi, Hang
Abstract: The tenderization mechanism in sea cucumber Apostichopus japonicus was investigated. Effects of three kinds of protease inhibitors on proteolysis in the tenderized Apostichopus japonicus body wall (AJBW) were characterized . The protein profiles in AJBW were determined at 0 h (CON), 1 h (T_1h), 3 h (T_3h) and 12 h (T_12h) after tenderization by isobaric tags for relative and absolute analysis quantitation. Results indicated inhibitors of cysteine, serine protease and matrix metalloproteinase (MMP) could prevent the release of TCA-soluble peptides and hydroxyproline. Proteomic analysis revealed 1865, 857 and 1587 differential abundant proteins at T_1h, T_3h and T_12h, respectively. The expressions of key proteins including cathepsins, calpains, caspases, proteasomes and MMPs were upregulated. Furthermore, proteins involved in oxidative stress response, innate immune response, apoptosis and reorganization of cytoskeleton and extracellular matrix were upregulated, which could be the potential biomarkers. Our findings revealed important mechanism of tenderization in AJBW which will lead to better understanding of this important process. Graphical abstract: Unlabelled Image Highlights: Identify 2160 DAPs during tenderization. Key proteases were significantly upregulated during tenderization. Biological processes were induced during tenderization.